Reconstruction of Legal Policy through Strengthening Cross-Border Cooperation and Joint Intelligence in Efforts to Stem the Circulation of Narcotics from Abroad to Indonesia - Mario Pangihutan Sirait; Yundini Husni; Kif Aminanto (Indonesian Journal Publisher, 2026)
Transnational narcotics trafficking is a form of transnational organized crime that continues to grow and exploits weaknesses in border surveillance and limited coordination between countries in the law enforcement system. This study aims to analyze the effectiveness of legal regulations on cross-border cooperation and joint intelligence in stemming the circulation of narcotics from abroad to Indonesia and to formulate an ideal legal policy reconstruction in strengthening the transnational narcotics law enforcement system. This study employs a normative juridical method with a legislative approach and a conceptual approach through a study of Law Number 35 of 2009 concerning Narcotics, Law Number 17 of 2011 concerning State Intelligence, Law Number 1 of 2006 concerning Mutual Assistance in Criminal Matters, as well as the United Nations Convention against Illicit Traffic in Narcotic Drugs and Psychotropic Substances 1988, and various other international legal instruments. The research concludes that legal regulations governing cross-border cooperation and joint intelligence are already in place, yet their implementation remains ineffective due to regulatory fragmentation, weak inter-agency coordination, limited intelligence-sharing systems, sectorial interests, and inadequate border surveillance. Therefore, legal policy reconstruction is needed through harmonization of national and international regulations, strengthening cross-sectorial institutions and coordination, establishing a technology-based integrated intelligence system, and enhancing cross-border operational cooperation to create a more effective, adaptive, and responsive narcotics law enforcement system to address developments in transnational narcotics crime.